2008
DOI: 10.1590/s0034-89102008000500013
|View full text |Cite
|
Sign up to set email alerts
|

Violência doméstica na gravidez: prevalência e fatores associados

Abstract: OBJECTIVE:To identify the factors associated with domestic violence against pregnant women. METHODS:Interviews were conducted with 1,379 pregnant women undergoing antenatal care in basic health care units of the Brazilian Health System, within the municipality of Campinas (Southeastern Brazil). A structured questionnaire on domestic violence, validated in Brazil, was applied between July 2004 and July 2006. The fi rst and second interviews in a cohort study were analyzed. Descriptive and multiple logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
59
3
26

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 4 publications
8
59
3
26
Order By: Relevance
“…The lifetime prevalence of emotional or physical abuse was high in our study, a finding consistent with many Brazilian and international studies 66,67,68 . The prevalence of physical violence during pregnancy was similar to that reported in prior Brazilian studies 29,69,70 . This violence is mainly committed by intimate partners, and is an important risk factor for depression in women 5,7,29,70,71,72,73,74 .…”
Section: Factorsupporting
confidence: 86%
See 1 more Smart Citation
“…The lifetime prevalence of emotional or physical abuse was high in our study, a finding consistent with many Brazilian and international studies 66,67,68 . The prevalence of physical violence during pregnancy was similar to that reported in prior Brazilian studies 29,69,70 . This violence is mainly committed by intimate partners, and is an important risk factor for depression in women 5,7,29,70,71,72,73,74 .…”
Section: Factorsupporting
confidence: 86%
“…The prevalence of physical violence during pregnancy was similar to that reported in prior Brazilian studies 29,69,70 . This violence is mainly committed by intimate partners, and is an important risk factor for depression in women 5,7,29,70,71,72,73,74 . Additionally, gender-based violence has adverse consequences for fetal and maternal survival 29,69,72,73 .…”
Section: Factorsupporting
confidence: 86%
“…Another study conducted in Rio de Janeiro revealed that physical violence was more frequent against adolescent pregnant women who had a low educational level, did not work outside the home, had fewer prenatal appointments, had low levels of social support, were from low-income families, had three or more children aged less than five and who reported use of alcohol 11 . In Campinas (São Paulo), pregnant women with low schooling and women who were heads of their household were more exposed to physical and sexual violence 12 . In another study in Rio de Janeiro, physical violence was more frequent among pregnant adolescents who reported use of alcohol 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have used bivariate or multivariable analyses by means of logistic regression 4,5,11,12,13 . There are criticisms of this type of analysis because it only investigates direct relationships between explanatory variables and an outcome, not allowing for the evaluation of intermediate paths, i.e., indirect or mediation effects 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Entre as gestantes, estudos brasileiros recentes encontraram índices de violência variando entre 5,1 e 19,1%. [2][3][4] Estes dados sugerem o alto impacto da VCM na saúde e na vida individual, familiar e coletiva com repercussões sócioe-conomicas e políticas. 5 Apesar de sua alta prevalência, a VCM é pouco identificada nos serviços de saúde, sendo caracterizada como um problema extremamente difícil de ser abordado.…”
Section: Introductionunclassified